2022
DOI: 10.4314/jae.v26i1.5
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting use of information communication technologies among extension agents in North-East, Nigeria

Abstract: The study identified the levels of ICT use, awareness, accessibility, perceived organizational support, assessed the perception of the respondents on problems in using ICTs for agriculture extension work and, clarifies the relationships between awareness, accessibility, perceived organizational support, and use of ICTs. Data were collected through the use of a questionnaire distributed to 254 respondents using a multi-stage sampling and stratified sampling procedures. Mean, frequency, standard deviation and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Enhancing farmers' access to valuable agricultural information leads to higher productivity and sustainability (Sa'adu et al, 2022). Extension methods used in technology transfer could be individual, group and mass media (Ariyo, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Enhancing farmers' access to valuable agricultural information leads to higher productivity and sustainability (Sa'adu et al, 2022). Extension methods used in technology transfer could be individual, group and mass media (Ariyo, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…These are merely the initial steps, though, and further research and execution are needed. Even with the automation of accounting, the requirement for an accountant-bookkeeper has started to decline and is now entirely replaced by an accountant operator who inputs raw data into the information system (Mustapha, et al, 2020). The future of the accounting profession is being seen in oppositional ways as a result of this circumstance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Access level to agricultural credit is the percent of smallholder farmers able to receive agricultural credit to be used in farm production [15]. Tiwari [8] reported that smallholder farmers require funds to buy ICT tools and maintain them in good working conditions as well as subscribe to agricultural extension services.…”
Section: Access Level To Agricultural Creditmentioning
confidence: 99%
“…In Kenya, especially in Rangwe Sub-County, access to credit from money lending institutions is accredited as a significant accelerator in agricultural technology adoption like the use of ICT tools. The smallholder farmers may access credit from public and private institutions such as banks, farmer groups, friends, and relatives [15]. Çetin et al [20] found that some of the smallholder farmers who had used mobile phones to share agricultural information had not received agricultural credit from any source.…”
Section: Sources Of Agricultural Credit and Correlationmentioning
confidence: 99%